Annual Summary of Weather Data for Parsons – 2017 - M. Knapp; L. W. Lomas (Kansas Agricultural Experiment Station Research Reports, 2018)
Weather Data for Parsons – 2017
Keywords: weather; Parsons weather; 2017 weather